PERANAN BUMDES UNIT USAHA FUTSAL DALAM PEMBANGUNAN MASYARAKAT DI DESA KALIBU KECAMATAN KULISUSU KABUPATEN BUTON UTARA - Zainuddin, Muh Zabir; HM, Suyuti; Djauhar, Asri; Taufik, Ali (Sultra Journal of Economic and Business, 2022)
Knowing the profit level of the futsal field tenant business (BumDes) in the village of Kalibu, Kulisusu sub-district, North Buton Regency.Knowing the business feasibility of a futsal field tenant (BumDes) in Kalibu Village, Kulisusu District, North Buton RegencyThis study aims to find out what the profit level of a futsal field tenant business is and how the feasibility of a futsal field tenant business is in Kalibu Village, Kulisusu District, North Buton Regency. This study uses descriptive data analysis, which presents data according to the information obtained in the field. The data in this research are primary and secondary data. As for the results of this study, the calculation of the R/C ratio of the Futsa Field Tenant Business (BUMDes) in Kalibu Village, Kulisusu District, North Buton Regency, that the Futsa Field Business (BUMDes) is feasible to run. The head or manager of the BUMDes business unit has the task of assisting the director in managing, developing and managing BUMDes businesses that are in accordance with the potential of the village and the needs of the community.